Variable retention forestry conserves habitat of bird species in Patagonian Nothofagus pumilio forests - Lencinas, María Vanessa (2018)
Variable retention is an alternative harvesting system that could be implemented instead the more traditional ones (e.g. shelterwood cut for N. pumilio forests in southern Patagonia), because it was designed not only for timber purpose, but also for conservation. However, the impact of different retention types on diversity is not clear, e.g. stenotopic and eurytopic bird species. The objective of this work was to analyse the habitats (inside, edge or outside of aggregated retention) and the use of strata (canopy, stem, debris and floor) for different bird species under two different variable retention harvesting types (aggregated + dispersed retentions, or aggregated retention + clear-cuts). We analysed four years of bird observation data in variable retention harvested and unharvested forest permanent plots located in Tierra del Fuego province (Argentina) belonging to PEBANPA (Parcelas de Ecología y Biodiversidad de Ambientes Naturales en Patagonia Austral) network, also with understory and crown cover data. Statistical analysis included uni-and multivariate tests, and comparisons with unharvested forests. We inventoried nine bird species, six of which showed significantly different habitat preference in variable retention types (Carduelis barbata, Phrygilus patagonicus and Tachycineta leucopyga in aggregated + dispersed retentions, and Enicognathus ferrugineus, P. patagonicus, T. leucopyga, Troglodytes aedon and Zonotrichia capensis in aggregated retention + clear-cuts). Likewise, all evaluated species presented differential use of strata, and some species changed comparing harvested and unharvested forests. DCA (Detrended Corresponded Analysis) highlighted association between species and habitats (e.g. P. patagonicus is more related to outside aggregated retentions) as well as differences between variable retention types, showing that bird species move toward edges when clear-cuts were carried out, among aggregated retention, instead of dispersed retention. These results support the effectiveness of the variable retention to conserve habitat of bird species inside managed forests, which satisfy both stenotopic and eurytopic species requirements.